2016
DOI: 10.1039/c6ra03926j
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic inhibitory effects of naproxen in combination with magnolol on TPA-induced skin inflammation in mice

Abstract: A combination of naproxen and magnolol effectively inhibited TPA-induced skin inflammation via blocking PI3K/Akt and PI3K/PKC signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It has been well established activation of Akt/IKK signaling pathway results in NF‐κB activation (Yue et al, 2016). In this study, we also verified whether such synergism is specific to the Akt/IKK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well established activation of Akt/IKK signaling pathway results in NF‐κB activation (Yue et al, 2016). In this study, we also verified whether such synergism is specific to the Akt/IKK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental evidence has shown that exposure of skin to TPA induces the activation of intracellular pathways through the activation of protein kinase C (PKC), including PI3K/AKT/NF-κB signaling, STAT3 signalling, as well as the generation of inflammatory cytokines (Lai et al, 2007;Yue et al, 2016;Rakariyathama et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were pre‐approved by the center of animal test of Sun Yat‐sen University. Mouse inflammatory tests were conducted using the method of Yue et al . Various concentrations of the EOs (25, 50, and 100 mg/kg) were prepared in peanut oil.…”
Section: Methodsmentioning
confidence: 99%